2015
DOI: 10.1113/jphysiol.2014.288209
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol modulates open probability and desensitization of NMDA receptors

Abstract: Key pointsr NMDA receptors (NMDARs) are tetrameric cation channels permeable to calcium; they mediate excitatory synaptic transmission in the CNS and their excessive activation can lead to neurodegeneration.r Although these receptors are in direct contact with plasma membrane, lipid-NMDAR interactions are little understood.r Using cultured rat cerebellar granule cells, we show that acute and chronic pretreatments resulting in cell cholesterol depletion profoundly diminish NMDAR responses and increase NMDAR des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
89
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 57 publications
9
89
0
Order By: Relevance
“…In a recent study, the physiological role of membrane lipids in the modulation of NMDAR activity was shown . In that study, it was shown that acute and chronic pretreatments resulting in cell cholesterol depletion profoundly diminished NMDAR responses and increased NMDAR desensitization in cultured rat cerebellar granule cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the physiological role of membrane lipids in the modulation of NMDAR activity was shown . In that study, it was shown that acute and chronic pretreatments resulting in cell cholesterol depletion profoundly diminished NMDAR responses and increased NMDAR desensitization in cultured rat cerebellar granule cells.…”
Section: Discussionmentioning
confidence: 99%
“…(i) The x ‐axis shows the total concentration of applied glycine including 0.04 μM of background glycine (Korinek et al . ). Dose–response curves for glycine are nearly identical between control‐treated and lectin‐treated CGC s, including the calculated values of the EC 50 (control: 1.7 ± 0.2 μM; AAL : 2 ± 0.3 μM; WGA : 1.5 ± 0.3 μM; ConA: 1.5 ± 0.3 μM; n ≥ 5; p > 0.05; anova ).…”
Section: Resultsmentioning
confidence: 97%
“…The calculated values of the EC 50 for NMDA (control: 112.5 AE 7.0 lM; AAL: 200.6 AE 13.4 lM; WGA: 188.6 AE 29.0 lM; ConA: 180.6 AE 21.4 lM; n ≥ 5) obtained from lectin-treated CGCs significantly differed from the control CGCs (p < 0.05; ANOVA; Student-Newman-Keuls method). (i) The x-axis shows the total concentration of applied glycine including 0.04 lM of background glycine(Korinek et al 2015). Dose-response curves for glycine are nearly identical between control-treated and lectin-treated CGCs, including the calculated values of the EC 50 (control: 1.7 AE 0.2 lM; AAL: 2 AE 0.3 lM; WGA: 1.5 AE 0.3 lM; ConA: 1.5 AE 0.3 lM; n≥ 5; p > 0.05; ANOVA).…”
mentioning
confidence: 99%
“…Further, their activity is modulated by an array of small ions and molecules (protons, Zn 2+ , spermine) [1, 6], membrane lipids [7], as well as post-translational modifications such as phosphorylation [8]. Missense mutations distributed throughout NMDAR subunits have recently been associated with devastating neurological disorders [9, 10].…”
Section: One Ion Channel Protein Many Conformationsmentioning
confidence: 99%